Modern approaches to the correction of hemodynamic disorders in patients with severe combined trauma (Perioperaciina Medicina, 2020)
Background. The choice of a rational program of infusion therapy for severe trauma remains an urgent problem. Crystalloid solutions are used as the main infusion media, but data on the effect of balanced multicomponent solutions on the hemodynamic profile in patients with severe trauma in the literature are almost absent.The aim: to investigate the possibility of correction of hemodynamic disorders in patients with severe combined trauma with the use of a modern multicomponent drug based on a 6% solution of sorbitol (reosorbilact).Material and methods: a total of 60 patients with severe combined trauma and the clinic of degree I–II traumatic shock aged 18 to 46 years were examined. Patients were divided into two groups: 1st group (n = 30) – patients who included in the standard complex of intensive care (IС) reosorbilact at a dose of 8–10 ml/kg body weight; 2nd group (n = 30) – patients who underwent a standard IС complex.Results: administration of reosorbilact resulted in a decrease in extracellular fluid volume, an increase in BCC and a transition from hypokinetic to eukinetic circulation within 3 hours of infusion and persisted for up to 6 hours after infusion (p < 0.01). The introduction of adrenomimetics were required: before the study in groups 1 and 2 – 7 (23.3 %) and 6 (20.0 %) patients, after 6 hours – respectively 1 (3.3 %) and 4 (13.3 %), and one day after the introduction of reosorbilact no patient required the introduction of adrenomimetics, whereas in group 2 such patients were 3 (10.0 %, p < 0.05).Conclusions. The use of balanced multicomponent solutions based on sorbitol is accompanied by a change in the hypokinetic type of blood circulation to eukinetic, lack of interhydration hyperhydration, rapid stabilization of hemodynamic parameters and reduced need for adrenomimetic support. Conflict of interest: absent
Keywords: severe trauma; infusion therapy; reosorbilact